The shaping of America : a geographical perspective on 500 years of history - Meinig, D. W. (Donald William), 1924-2020 (Yale University Press, 1986)
Volume one examines how an immense diversity of ethnic and religious groups ultimately created a set of distict regional societies. Volume two emphasises the flux, uncertainty, and unpredictablilty of the expansion into continental America, showing how a multitude of individuals confronted complex and problematic issues.